Corporate Governance to Prevent Financial Distress Evidence from Corporate Governance Perceptions Index of Indonesian Companies - Teti Rahmawati; Yana Hendriyana (Universitas Kuningan, 2018)
This study aims to determine the influence of Good Corporate Governance (GCG), Company Size, Liquidity, and Rentability on Financial Distress of companies listed on Corporate Governance Perception Index (CGPI) partially and simultaneously. The population of this research is companies listed on the Indonesian Stock Exchange (BEI) and Corporate Governance Perception ranks starting from 2013 to 2016. Based on the criteria above, 59 companies are selected. The sampling of this research is taken by using purposive sampling method from the population with a target of several considerations. The result shows that Good Corporate Governance does not significantly influence Financial Distress, Company Size negatively affects Financial Distress, Liquidity positively affects Financial Distress, and Rentability positively affects Financial Distress. Good Corporate Governance, Company Size, Liquidity, and Rentability partially influence Financial Distress with coefficient determination is 92,25% while 2,75% is explained by other unobserved variables in outside the model.